Methoxetamine toxicity reported to the National Poisons Information Service: clinical characteristics and patterns of enquiries (including the period of the introduction of the UK's first Temporary Class Drug Order). Issue 1 (24th January 2013) - Hill, Simon L; Harbon, Siân C D; Coulson, James; Cooper, Gillian A; Jackson, Gill; Lupton, David J; Vale, J Allister; Thomas, Simon H L
Abstract : Objective: To report the demographic and clinical characteristics of cases of methoxetamine toxicity reported to The National Poisons Information Service (NPIS) by healthcare professionals. To assess the pattern of enquiries from health professionals to the UK NPIS related to methoxetamine, including the period of the making of the UK first Temporary Class Drug Order (TCDO). Methods: All telephone enquiries to and user sessions for TOXBASE, the NPIS on-line information resource, related to methoxetamine (and synonyms 'MXE', 'mket' and '2-(3-methoxyphenyl)-2-(ethylamino)cyclohexanone') were reviewed from 1 April 2010 to 1 August 2012. Data were compared for the 3 months before and after the TCDO. Results: There were 47 telephone enquiries and 298 TOXBASE sessions regarding methoxetamine during the period of study. Comparing the 3 months before and after the TCDO, TOXBASE sessions for methoxetamine fell by 79% (from 151 to 32) and telephone enquiries by 80% (from 15 to 3). Clinical features reported by enquirers were consistent with case reports of analytically confirmed methoxetamine toxicity and typical toxidromes were of stimulant (36%), reduced consciousness (17%), dissociative (11%) and cerebellar (6.4%) types, but also particularly featured acute disturbances in mental heath (43%). Conclusions: Structured NPIS data may reveal trends in drugs of abuse use and toxicity when interpreted within their limitations. Since April 2012, there have been fewer enquiries to NPIS from clinicians, indicating reduced presentations with suspected methoxetamine toxicity to healthcare services. It is unclear if this is related to the TCDO made on 5 April 2012.